Tuning the permselectivity of polymeric desalination membranes via control of polymer crystallite size - Xinglin Lu (Nature Portfolio, 2019)
Increasing the selectivity of desalination membranes is of crucial importance for advancing membrane desalination technologies. Here the authors demonstrate a plasticizing-extracting process for tuning the permselectivity of polymeric membranes and achieving desired desalination performance.